Comparison of skin pressure measurements with the use of pelvic circumferential compression devices on pelvic ring injuries. Issue 3 (March 2016) - Prasarn, Mark L.; Horodyski, MaryBeth; Schneider, Prism S.; Pernik, Mark N.; Gary, Josh L.; Rechtine, Glenn R.
Abstract: Objectives: Pelvic circumferential compression devices are commonly used in the acute treatment of pelvic fractures for reduction of pelvic volume and initial stabilisation of the pelvic ring. There have been reports of catastrophic soft-tissue breakdown with their use. The aim of the current investigation was to determine whether various pelvic circumferential compression devices exert different amounts of pressure on the skin when applied with the force necessary to reduce the injury. The study hypothesis was that the device with the greatest surface area would have the lowest pressures on the soft-tissue. Methods: Rotationally unstable pelvic injuries (OTA type 61-B) were surgically created in five fresh, whole human cadavers. The amount of displacement at the pubic symphysis was measured using a Fastrak, three-dimensional, electromagnetic motion analysis device (Polhemus Inc., Colchester, VT). The T-POD, Pelvic Binder, Sam Sling, and circumferential sheet were applied in random order for testing. The devices were applied with enough force to obtain a reduction of less than 10 mm of diastasis at the pubic symphysis. Pressure measurements, force required, and contact surface area were recorded with a Tekscan pressure mapping system. Results: The mean skin pressures observed ranged from 23 to 31 kPa (173 to 233 mm of Hg). The highest pressures were observed with the Sam Sling, but no statistically significant skin pressure differences were observed with any of the four devices ( p > 0.05). The Sam Sling also had the least mean contact area (590 cm 2 ). In greater than 70% of the trials, including all four devices tested, skin pressures exceeded what has been shown to be pressure high enough to cause skin breakdown (9.3 kPa or 70 mm of Hg). Conclusions: Application of commercially available pelvic binders as well as circumferential sheeting commonly results in mean skin pressures that are considered to be above the threshold for skin breakdown. We therefore recommend that these devices only be used acutely, and definitive fixation or external fixation should be performed early as patient physiology allows. There may be some advantage of use of a simple sheet given its low cost, versatility, and ability to alter contact surface area.